Efektivitas Online Shop terhadap Kemudahan Belanja Mahasiswa di Yogyakarta - Pratama, Muhammad Rizqi; Khotimah, Intan Nur; Taqya, Rona Huriya (ARZUSIN, 2024)
This study aims to examine the influence of Online Shop Effectiveness and Ease of Online Shopping on the shopping experience of students in Yogyakarta. In an increasingly digital era, students, as a group heavily reliant on technology, are opting for e-commerce platforms to fulfill their shopping needs. This research uses a quantitative approach with a sample of 105 students living in Yogyakarta. Data were collected through questionnaires, which were tested using validity, reliability, normality, and hypothesis testing. The results show a significant influence of Online Shop Effectiveness and Ease of Online Shopping on students' satisfaction and convenience in online shopping, with a significance value of 0.00. These findings indicate that factors such as ease of navigation, fast delivery, and flexible payment methods contribute significantly to a positive shopping experience for students. The implications of this research provide insights for e-commerce platform managers to improve their services to meet the growing demand of the student market. This study also contributes to the development of the Technology Acceptance Model (TAM) theory in the context of e-commerce in Indonesia.